The impact of the ‘hub and spoke’ model of care for lung cancer and equitable access to surgery - Khakwani, Aamir; Rich, Anna L.; Powell, Helen A.; Tata, Laila J.; Stanley, Rosamund A.; Baldwin, David R.; Duffy, John P.; Hubbard, Richard B. (BMJ Publishing Group, 2014)
Objectives: To determine the influence of where a patient is first seen (either surgical or non-surgical centre) and patient features on having surgery for non-small cell lung cancer (NSCLC).